Drying performance and physical properties of air dried oil palm wood - Zainun, Farizatul Shahira (2019)
Air Drying is the method used to dry Oil Palm Wood (OPW) at open air area until achieved the Equilibrium Moisture Content (EMC). This conventional air drying method takes longer time compared to advanced drying method such as Air Forced Drying where the drying of OPW is done by forcing the air circulation towards the OPW by setting the range of air velocity. Air Drying Method for OPW affect the quality of the lumber where results in high number of defects due to the high moisture content, long drying periods and nature of OPW. In this study, Air Drying Method was used to evaluate the drying rate and drying defect of air dried OPW based on different thickness and portion. The thickness used were 3cm and 5cm thick for both outer and inner portion of trunk which were differentiate based on initial moisture content. The samples were cut into desired dimensions and undergo air drying for some duration of months. The drying rate of OPW then was calculated with formula based on the daily weighed of sample. Thus, these findings showed inner portion of OPW with 3cm and 5cm thick gave most drying defect and highest in drying rate than outer portion.